All Days 2010
DOI: 10.2118/134823-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Gas Production in Coal Bed Methane Formations With Zeta Potential Altering System

Abstract: This paper describes lab studies and field results on how a new Zeta Potential Altering System (ZPAS), utilized in fracturing treating fluids, improves gas rate production. Lab and field results show ZPAS minimizes proppant flow back and coal fines migration, enhances fluid load recovery, and inhibits calcium carbonate scale formation. The mechanism of this system based on an inner salt that modifies the Zeta Potential on particles such as frac sand and formation substrate, changing the charge towards neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Due to hydrophobe interactions through VDW bonds, a strong molecular hook-and-latch system is formed between fines and the fracture surface, thus providing an increased adhesive force . Several experimental and field studies have demonstrated that chemical methods successfully prevent fines migration, even under high flow rates and flow interruptions, with no observed reduction in permeability. …”
Section: Implications For Field-scale Fines Controlmentioning
confidence: 99%
“…Due to hydrophobe interactions through VDW bonds, a strong molecular hook-and-latch system is formed between fines and the fracture surface, thus providing an increased adhesive force . Several experimental and field studies have demonstrated that chemical methods successfully prevent fines migration, even under high flow rates and flow interruptions, with no observed reduction in permeability. …”
Section: Implications For Field-scale Fines Controlmentioning
confidence: 99%